2020
DOI: 10.21037/sci-2020-020
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen induces stem-like phenotypes and multidrug resistance by altering epigenetic regulators in ERα+ breast cancer cells

Abstract: Background: To understand the mechanism underlying tamoxifen-induced multidrug resistance (MDR) and stem-like phenotypes in breast cancer cells, we treated the MCF-7 cells with 4-hydroxy-tamoxifen (TAM) for 6 months continuously and established MCF-7 tamoxifen resistance (TR) phenotypes.Methods: In the present study, the following methods were used: cell viability assay, colony formation, cell cycle analysis, ALDEFLUOR assay, mammosphere formation assay, chromatin immunoprecipitation (ChIP) assay, PCR array… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The tumour formation at the secondary site reflects the stemness potential of cancer cells, which can be tracked via detecting the colony-forming potential ( Sharma et al, 2022 ). The exposure of tamoxifen in MCF-7 cells resistant to tamoxifen (MCF7-TR) resulted in an increased number of CSCs as observed by the increased number of ALDH+ cells accompanied by increased colony formation, a higher number of mammospheres, and alterations in epigenetic and multidrug resistance (MDR) stem cell marker genes ( Kalyanaraman et al, 2020 ). In addition, radioresistant breast cancer cells (RT-R-MDA-MB-231) showed increased colony formation and expression of CD44 and other markers of CSCs such as Notch, ALDH1, or OCT3/4 ( Ko et al, 2018 ).…”
Section: Breast Cancer Stem Cells (Bcscs)mentioning
confidence: 99%
“…The tumour formation at the secondary site reflects the stemness potential of cancer cells, which can be tracked via detecting the colony-forming potential ( Sharma et al, 2022 ). The exposure of tamoxifen in MCF-7 cells resistant to tamoxifen (MCF7-TR) resulted in an increased number of CSCs as observed by the increased number of ALDH+ cells accompanied by increased colony formation, a higher number of mammospheres, and alterations in epigenetic and multidrug resistance (MDR) stem cell marker genes ( Kalyanaraman et al, 2020 ). In addition, radioresistant breast cancer cells (RT-R-MDA-MB-231) showed increased colony formation and expression of CD44 and other markers of CSCs such as Notch, ALDH1, or OCT3/4 ( Ko et al, 2018 ).…”
Section: Breast Cancer Stem Cells (Bcscs)mentioning
confidence: 99%
“…Breast cancer (BC) has one of the highest rates of cancer deaths among women worldwide, with long-term exposure to estrogen considered to be the principal factor leading to its tumorigenesis; estrogen-dependent BC accounts for approximately 2/3 of BC cases ( 1 , 2 ). In addition, clinical research using anti-estrogens or aromatase inhibitors to reduce local and distant recurrence has revealed that estrogen promotes the development of BC ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Under the current level of medical care, the 5-year survival rate of breast cancer patients can reach more than 89 %. Such good therapeutic effect of breast cancer is mainly attributed to the emergence of a large number of estrogen receptor (ERα) antagonist drugs in recent years, such as tamoxifen and raloxifene [3], the most commonly used drugs in the clinical treatment of breast cancer.…”
Section: Introductionmentioning
confidence: 99%